Flesh-Eating Disease: A Note on Necrotizing Fasciitis. (1st June 2001) - Davies, H Dele
Abstract : There has been much media attention in the past few years to the condition dubbed 'flesh-eating disease', which refers, primarily, to a form of invasive group A beta hemolytic streptococcal (GABHS) infection that leads to fascia and muscle necrosis. In 1999, the Canadian Paediatric Society issued a statement on the state of knowledge and management of children, and close contacts of persons with all-invasive GABHS disease (1). The present note is intended to deal specifically with necrotizing fasciitis (NF) by providing an update on the limited current state of knowledge, diagnosis and management. Surveillance to establish actual national rates and epidemiology of NF through the Canadian Paediatric Society is proposed.